Multiwavelength Pulsations and Surface Temperature Distribution in the Middle-aged Pulsar B1055–52 - Armin Vahdat; B. Posselt; G. G. Pavlov; P. Weltevrede; A. Santangelo; S. Johnston (The Astrophysical Journal, 2024)
We present a detailed study of the X-ray emission from PSR B1055–52 using XMM-Newton observations from 2019 and 2000. The phase-integrated X-ray emission from this pulsar is poorly described by existing models of neutron star atmospheres. Instead, we confirm that, similar to other middle-aged pulsars, the best-fitting spectral model consists of two blackbody components, with substantially different temperatures and emitting areas, and a nonthermal component characterized by a power law. Our phase-resolved X-ray spectral analysis using this three-component model reveals variations in the thermal emission parameters with the pulsar’s rotational phase. These variations suggest a nonuniform temperature distribution across the neutron star’s surface, including the cold thermal component and probable hot spot(s). Such a temperature distribution can be caused by external and internal heating processes, likely a combination thereof. We observe very high pulse fractions, 60%–80% in the 0.7–1.5 keV range, dominated by the hot blackbody component. This could be related to temperature nonuniformity and potential beaming effects in an atmosphere. We find indication of a second hot spot that appears at lower energies (0.15–0.3 keV) than the first hot spot (0.5–1.5 keV) in the X-ray light curves and is offset by about half a rotation period. This finding aligns with the nearly orthogonal rotator geometry suggested by radio observations of this interpulse pulsar. If the hot spots are associated with polar caps, a possible explanation for their temperature asymmetry could be an offset magnetic dipole and/or an additional toroidal magnetic field component in the neutron star crust.